To check his answer, Jason can substitute the value he found for \( x \) back into the original equation to verify if both sides of the equation are equal. Here are the steps he would follow:
-
Start with the original equation: \[ -8.5x - 3.5x = -78 \]
-
Substitute \( x = 6.5 \) into the equation: \[ -8.5(6.5) - 3.5(6.5) \]
-
Calculate each term:
- Calculate \( -8.5(6.5) \): \[ -8.5 \times 6.5 = -55.25 \]
- Calculate \( -3.5(6.5) \): \[ -3.5 \times 6.5 = -22.75 \]
-
Add the calculated terms together: \[ -55.25 - 22.75 = -78 \]
-
Compare the result with the right side of the original equation:
- The left side equals \(-78\) and the right side is \(-78\).
Since both sides of the equation are equal, Jason can conclude that his solution \( x = 6.5 \) is correct.